Book Review of "The Business of Life: An “Inside-Out” Approach to Building a More Successful Financial Planning Practice" - Dan Danford (Journal of Financial Therapy, 2011)
Kay, Michael (2011). The Business of Life: An “Inside-Out” Approach to Building a More Successful Financial Planning Practice. Sunnyvale, CA: AdvisorPress. ISBN: 978-1603530217. Although the book is written to ultimately help consumers, financial advisors and therapists can learn how Kay examines values, goals, dreams, and priorities to create an ideal practice. Kay makes a strong case for the kind of in-depth relationships that combine life and financial planning, something termed Financial Life Planning. FLP is not a new idea, necessarily, but this book provides a step-by-step practice framework for those interested in adopting it. The book is a welcome addition to the financial therapist’s planning tools and techniques workbench.
Keywords: Financial Therapy; Kay